2012
DOI: 10.1007/s11695-012-0651-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile of Clinically Severe Obese Patients

Abstract: The clinically severe obese patients showed low BMR levels when adjusted per kilogram per body weight. Body composition may influence BMR. The use of the MSJE formula may be helpful in those cases where it is impossible to use IC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 38 publications
1
36
0
3
Order By: Relevance
“…However, it should be noted that weight loss in general is associated with metabolic slowing exemplified by decrease in resting metabolic rate . Slowing of the metabolism results in slower weight loss and a risk of weight regain . Therefore, it is possible that (in general) patients with less slowing of metabolism have more weight loss and increases in tNAA/tCr, whereas patients with more pronounced slowing of metabolism experience less weight loss and decrease of tNAA/tCr.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that weight loss in general is associated with metabolic slowing exemplified by decrease in resting metabolic rate . Slowing of the metabolism results in slower weight loss and a risk of weight regain . Therefore, it is possible that (in general) patients with less slowing of metabolism have more weight loss and increases in tNAA/tCr, whereas patients with more pronounced slowing of metabolism experience less weight loss and decrease of tNAA/tCr.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, it was believed that obesity was associated with "slow metabolism" due to lower RMR, AEE, and/or DIT contributing to a positive energy balance and subsequent weight gain [30]. Nonetheless, studies conducted over the past three decades have reported that absolute EE in obese individuals is in fact higher compared to their lean counterparts [43][44][45][46][47][48][49].…”
Section: Energy Expenditure In Obesitymentioning
confidence: 99%
“…RMR is positively associated with weight [43][44][45][46][47][48]50,51] with reported differences up to 800 kcal/day when comparing individuals with a BMI N50 (RMR = 2157 kcal/day) to lean individuals (RMR = 1331 kcal/day) [47]. In obesity, increases in fat mass occur concurrently with increases in FFM [45].…”
Section: Energy Expenditure In Obesitymentioning
confidence: 99%
“…The mechanism of action likely involves stimulation of gastric mechanoreceptors triggering short-acting vagal signals to brain regions implicated in satiety [5]. Resting metabolic rate (RMR) is elevated among obese individuals; compared with healthyweight individuals it was shown to decrease with weight loss induced by dietary and/or physical activity interventions [6][7][8][9][10][11][12]. However, increases in RMR of individual patients were reported [13].…”
mentioning
confidence: 99%
“…However, increases in RMR of individual patients were reported [13]. RMR divided by current weight (RMR/mass) [10,14] is lower among obese individuals, compared with individuals who are overweight or at normal weight [12]. After diet-restriction therapies accompanied by vigorous physical exercise, RMR/mass was reported to decrease [9] or increase (in an extreme case of 35% loss of initial weight) [7].…”
mentioning
confidence: 99%